Evidence of the protein content of bovine and human dental pulps by the action of endodontic irrigation solutions through electrophoretic patterns - María E López; María M Salas; María L De La Casa (Wolters Kluwer Medknow Publications, 2013)
Background: Sodium dodecyl sulfate polyacrylamide gel electrophoresis let to show the protein content of different tissues. Dental pulp contains connective tissue which is removed during the endodontic treatment. Many studies consider bovine rather than human pulp tissue because of its size. Aim: To evidence the protein content of bovine and human dental pulps and the action of endodontic irrigation solutions through electrophoretic patterns. Materials and Methods: Extracts of human and bovine dental pulps were prepared. Sodium hypochlorite, calcium hydroxide, chlorhexidine and ethylenediamine tetraacetic acid were used as irrigating solutions. Results: Bovine and human pulps have a small difference in two bands of proteins present between 74 kDa and 80 kDa. The denaturizing capacity of sodium hypochlorite and the washing action of calcium hydroxide and chlorhexidine were evidenced. Ethylenediamine tetraacetic acid solution was shown to contain proteins continuously during the endodontic root canal washing. Conclusions: Differences in pulp tissues and the action of irrigating solutions on their protein content would help on the understanding of the biological process of the endodontic treatment.